Teamwork and team performance in multidisciplinary cancer teams: development and evaluation of an observational assessment tool. - Lamb, B; Wong, H; Vincent, C; Green, J; Sevdalis, N (2011)
AIM: Team performance is important in multidisciplinary teams (MDTs), but no tools exist for assessment. Our objective was to construct a robust tool for scientific assessment of MDT performance. MATERIALS AND METHODS: An observational tool was developed to assess performance in MDTs. Behaviours were scored on Likert scales, with objective anchors. Five MDT meetings (112 cases) were observed by a surgeon and a psychologist. The presentation of case history, radiological and pathological information, chair's effectiveness, and contributions to decision-making of surgeons, oncologists, radiologists, pathologists and clinical nurse specialists (CNSs) are analysed via descriptive statistics, a comparison of average scores (Mann-Whitney U) to test interobserver agreement and intraclass correlation coefficients (ICCs) to further assess interobserver agreement and learning curves. RESULTS: Contributions of surgeons, chair's effectiveness, presentation of case history and radiological information were rated above average (p ≤ 0.001). Contributions of histopathologists and CNS were rated below average (p ≤ 0.001), and others average. The interobserver agreement was high (ICC = 0.70+) for presentation of radiological information, and contribution of oncologists, radiologists, pathologists and CNSs; adequate for case history presentation (ICC = 0.68) and contribution of surgeons (ICC = 0.69); moderate for chairperson (ICC = 0.52); and poor for pathological information (ICC = 0.31). Average differences were found only for case-history presentation (p ≤ 0.001). ICCs improved significantly in assessment of case history, and Oncologists, and ICCs were consistently high for CNS, Radiologists, and Histopathologists. CONCLUSIONS: Scientific observational metrics can be reliably used by medical and non-medical observers in cancer MDTs. Such robust assessment tools provide part of a toolkit for team evaluation and enhancement.